Birmingham Hip Resurfacing: a retrospective cohort study of clinical, biochemical, and radiological outcomes in a non-designer centre at minimum 15 years’ follow-up - Martin S. Davey; Conor Farrell; Conor Kilkenny; Conor Medlar; Niall P. McGoldrick; John F. Quinlan (Bone & Joint Open)
Aims: Although the use of metal-on-metal (MoM) implants in total hip arthroplasty (THA) remains a topic of controversy, prior literature has reported satisfactory ten-year clinical and radiological outcomes following Birmingham Hip Resurfacing (BHR), subsequently resulting in a recent Orthopaedic Data Evaluation Panel (ODEP) rating of 15 A*. Therefore, the purpose of this study was to evaluate the functional outcomes, radiological outcomes, and revision rates following BHR at a minimum of 15 years’ follow-up in a non-designer centre. Methods: Two investigators performed a retrospective review to identify consecutive patients who underwent BHR in our institution over a seven-year period (2003 to 2009, at minimum 15 years’ follow-up) in a non-designer centre. Evaluation of clinical (Oxford Hip Scores (OHS)), biochemical (cobalt and chromium levels), and radiological (plain film radiographs) outcomes was carried out. Survivorship analysis was performed using Kaplan-Meier curves, with all-cause surgical revision defined as a definitive endpoint for analysis. Descriptive statistical analysis was carried out. Results: Overall, 96 patients (86 males) at a mean age of 51.4 years (SD 9.9; 27 to 69) underwent 105 BHR procedures (nine bilateral) with at least 15 years’ minimum follow-up. Mean OHS was 38.3 (SD 9.6; 17 to 48) at 15-year minimum follow-up. The overall survivorship was 94.3% at 15 years post BHR, with an all-cause revision rate of 5.7%. Only eight BHR prostheses (8.2%) had radiolucent lines on plain films, none of which were listed for revision at the time of latest follow-up, while 32 patients had undergone MRI at 170 months (SD 54.9; 6 to 249) post BHR, with evidence of fluid collection, aseptic lymphocyte-dominant vasculitis-associated lesion, and metallosis identified on the MRI of four patients, four patients, and one patient, respectively. For 98.4% (60/61) of patients, cobalt and chromium values were either within normal limits (68.9%, n = 42) or less than double the upper limit of normal (29.5%, n = 18). Conclusion: This study found that BHR demonstrates an acceptable survivorship of 94% at 15 years of minimum follow-up, with satisfactory clinical and radiological outcomes to reflect this low all-cause revision rate in a non-designer centre. Cite this article: Bone Jt Open 2025;6(4):413–418.